PERAN CROWDFUNDING SYARIAH DALAM PEMBERDAYAAN UMKM: ANALISIS HUKUM EKONOMI SYARIAH PADA PLATFORM BIZHARE.ID - Romlah, Siti (Bayani, 2025)
Islamic crowdfunding is a financial innovation based on information technology that adheres to Sharia principles, such as the prohibition of riba (interest), gharar (uncertainty), and maysir (speculation), and utilizes contracts such as musyarakah and mudharabah. Using a normative legal approach, this research examines the compatibility of Bizhare.id’s contract structure and operational practices with Islamic economic law and national regulations, including OJK Regulation No. 57/POJK.04/2020 and DSN-MUI Fatwa No. 140/2021. The findings reveal that Bizhare.id is not only legally and Sharia-compliant, but also contributes to expanding access to halal capital, promoting Sharia financial literacy, and fostering equitable and sustainable economic empowerment for MSMEs in Indonesia.